Perspectives on reasons for suicidal behaviour and recommendations for suicide prevention in Kenya: qualitative study - Linnet Ongeri; Miriam Nyawira; Symon M. Kariuki; Mary Bitta; Chris Schubart; Brenda W. J. H. Penninx; Charles R. J. C. Newton; Joeri K. Tijdink (BJPsych Open, 2023)
Background Little is known about the reasons for suicidal behaviour in Africa, and communities’ perception of suicide prevention. A contextualised understanding of these reasons is important in guiding the implementation of potential suicide prevention interventions in specific settings.